Analisis Nilai Religius Sastra Novel 99 Cahaya di Langit Eropa Karya Rangga Almahendra dan Hanum Salsabiela Rais Kajian: Nilai Religius Hubungan Manusia dengan Tuhan - Tioria Pasaribu; Zira Fatmaira (Journal on Education, 2023)
Literary work as a medium for the soul of an author who feels he has a duty to contribute as a messenger of moral or religious messages and human life on earth. An author is considered successful if he is able to convey moral and religious messages and life through the literary works he writes, so that the reader does not feel that he is being lectured or lectured, but without realizing the moral message in literary works. Religion refers more to the system of worship of God in terms of official, laws, ordinances, statutes, etc., as well as the organization of the overall interpretation of the Bible, which includes social levels. Express devotion to God, close your eyes, focus, surrender and prepare to listen to the Holy Word silently. Humans were created to worship Allah SWT by carrying out His commands and staying away from all His prohibitions. Human closeness to Allah SWT takes various forms, depending on each individual. However, humans created by Allah SWT are guided by the holy book of the Qur'an and adhere to the teachings of Islam. This research is a qualitative study of literature and activities carried out by collecting and analyzing research data from the novel 99 Lights in the Sky of Europe by Rangga Almahendra and Hanum Salsabiela Rais. In this study, the researcher first read in detail the novel 99 Lights in the Sky Europe by Rangga Almahendra and Hanum Salsabiela Rais. divine value approach. Found research results seen from. (1) looking for divine values related to humans and faith, (2) looking for divine values related to humans and worship, (3) seeking grateful values related to God with humans and (4) looking for patient values related to God with humans.